FAKTOR YANG MEMENGARUHI NIAT BERKUNJUNG KEMBALI WISATAWAN MEDIS ASAL INDONESIA KE MALAYSIA - Dewiangelline, Dewiangelline; Fahlevi, Renza; Sinambela, Fitriana Aidnilla (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze the factors influencing the intention of Indonesian medical tourists to visit Malaysia. This study examines the influence of relationship marketing and word of mouth on trust, as well as the influence of trust on revisit intention. The research approach used was quantitative, with data collected through questionnaires distributed to Indonesian medical tourists who had received treatment in Malaysia. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test the relationships between variables. The results showed that all hypotheses were accepted. Relationship marketing and word of mouth had a positive and significant effect on trust, while trust had a positive and significant effect on medical tourists' intention to revisit. These findings confirm that trust is a key factor in shaping medical tourist loyalty. Practically, the results of this study provide input for the Indonesian government and hospital management in formulating policies to strengthen domestic medical tourism by increasing trust and service quality.